Evolution of Machine Learning Algorithms on Autonomous Robots - Mainampati, Manasa; Chandrasekaran, Balasubramaniyan (2020 10th Annual Computing and Communication Workshop and Conference (CCWC), 2020)
In this paper, an overview of the use of machine learning algorithms on autonomous robotic systems is presented. The concept of hardware and software integration and development is explained through a small robot such as Turtlebot used in the examples taken. This paper presents a survey of how machine learning can be utilized on a hardware platform and is the initial stage of the research work. This is a work in progress and the next stage is using this literature survey towards developing research towards a comparison of machine learning algorithms on the Turtlebot.